Selecting Relocation of Land Use in Hot Mud Disaster Area by Applying Geo-Environmental Evaluation. Case study: Sidoarjo, East Java, Indonesia - Putra, Doni Prakasa Eka (2010)
Since Mny 29, 2006, a sea of hot ntwl has been *ushill* fra t the grotud in SidoarjLt, Ensf la|a, 35 kilo lelers soldh of Intlonesia's second largesl city, Surabn!a- D e to tltis disaster, npptulinntelV thauslnd ofpcople haae beett t'orced t'rom llrcir hontes be caloe 6AA ha af ln1ld afid aillages zacre submergetl, farmland urs rttined, bltsinesses altd sclfiols claseLl as the mLLd illu dnted lhc sLlrrounditg arel. Rtlacaliotl af the lntld ses afirl sllppattins ifrastrllclllres nr bt, ottl . inpot ta.,l tr . ul.],rfi thp ht, I t.t't ,u t. irability and enaironmcntal sltstiinability i]1 thi. tlis n5ter areI- In ordt:t ta select the stitLfule lacntio for Innd ltses dnLl ifiliasttuct res, aspctl af en|1il'anfi1erLtal geola*lfiusl bt tul1cerncd. Geo EttrironlLtfital patufielers such ds XealogicLtl lLazards and geological r$otLrcts sreused lo selcct the suilnbb relocdl iiLt tt.n. t '',,t\ ttiotl al 1tt. .t;t ,t l. I .1d t . - i o'tducfcil by npplyitlg sinpk oaerlatl tatitg nletlioll. Rtsult a.f this etahnliLtn sl](tias thnt the relacati)lt of fht ln d ses c!:ulhe diJftftntintcd ita t|lrce cdt egories; (i) high risk In11d 1lse/infrnsfn.tclure, nad urte r;tk li d Ltsc/infrnsttuchor atd lt)ro risk 10ru1 se/i1lffistrwl re, F-nch of lhcst catesories haoc tlit'ferenct nny' of rclocatialt sui!nhilillJ, hoiael)er all i)rf. t' ',,.' tl rth .,.in,i..a.t,ior,r, t,t,. tht ia.sf llrtt t'ran thc lrct nlud disn.ler nrea.